(untitled) (Indian Journal of Animal Production and Management, 2026)
This study investigated the effect of replacing part of the dietary protein with different levels of urea on the productive performance, egg traits, blood parameters, and gut microbiota in laying hens. A total of 144 Isa Brown hens were divided into four groups: a control group receiving a standard diet (T1), and three experimental groups receiving the same diet supplemented with T2 (0.4%), T3 (0.8%) or T4 (1.2%) urea. The results showed that the addition of 0.4% urea improved feed conversion ratio, body weight gain, and overall productivity. However, higher levels of urea (0.8% and 1.2%) negatively affected performance, which may be attributed to potential nitrogen toxicity. Urea supplementation did not significantly affect most external egg quality parameters such as egg weight and shell thickness, but it influenced internal quality by increasing albumen percentage and reducing yolk proportion at higher doses. Blood analysis showed that moderate urea increased albumin and globulin concentrations, suggesting improved protein metabolism. Microbiological analysis confirmed an increase in the proportion of Lactobacillus individuals at 0.4% urea, which was more abundant with higher proportions of E. coli. Such results indicate the need for close regulation of dietary urea to optimize its beneficial effects without impairing hen health and performance.